Introduction to managerial economics - II , 2nd year BMS-3rd semester - Venkatesh Parvatthi and shukla S. and others (Sheth Publ., Mumbai, 2003)
B.M.S.
ENGLISH
Keywords: Introduction to managerial economics - II , 2nd year BMS-3rd semester; B.M.S.; B.M.S.